Improving Delivery Behaviors During Exposure for Pediatric OCD: A Multiple Baseline Training Trial With Community Therapists. Issue 4 (July 2021) - Benito, Kristen G.; Herren, Jennifer; Freeman, Jennifer B.; Garcia, Abbe M.; Block, Paul; Cantor, Elizabeth; Chorpita, Bruce F.; Wellen, Brianna; Stewart, Elyse; Georgiadis, Christopher; Frank, Hannah; Machan, Jason
Highlights: We examined whether a new training tool, the Exposure Guide (EG), improved therapist behaviors. Results suggest the EG helped some therapists initially meet clinical benchmarks. Future studies will be needed to verify these preliminary findings. Abstract: This study tested whether a new training tool, the Exposure Guide (EG), improved in-session therapist behaviors (i.e., indicators of quality) that have been associated with youth outcomes in prior clinical trials of exposure therapy. Six therapists at a community mental health agency (CMHA) provided exposure therapy for 8 youth with obsessive–compulsive disorder (OCD). Using a nonconcurrent multiple baseline design with random assignment to baseline lengths of 6 to 16 weeks, therapists received gold-standard exposure therapy training with weekly consultation (baseline phase) followed by addition of EG training and feedback (intervention phase). The primary outcome was therapist behavior during in-session exposures, observed weekly using a validated coding system. Therapist behavior was evaluated in relation to a priori benchmarks derived from clinical trials. Additional outcomes included training feasibility/acceptability, therapist response to case vignettes and beliefs about exposure, and independent evaluator-rated clinical outcomes. Three therapists reached behavior benchmarks only during the EG (intervention) phase. Two therapists met benchmarks during the baseline phase; one of these subsequently moved away from benchmarks but met them again after starting the EG phase. Across all therapists, the percentage of weeks meeting benchmarks was significantly higher during the EG phase (86.4%) vs. the baseline phase (53.2%). Youth participants experienced significant improvement in OCD symptoms and global illness severity from pre- to posttreatment. Results provide initial evidence that adding the EG to gold-standard training can change in-session therapist behaviors in a CMHA setting.